2013
DOI: 10.1021/jp310354p
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Proton Transfer in Highly Sulfonated Poly(phenylene sulfone) Ionomers: An Ab Initio Study

Abstract: The need to operate proton exchange membrane fuel cells under hot and dry conditions has driven the synthesis and testing of sulfonated poly(phenylene) sulfone (sPSO(2)) ionomers. The primary hydration and energetics associated with the transfer of protons in oligomeric fragments of two sPSO(2)ionomers were evaluated through first-principles electronic structures calculations. Our results indicate that the interaction between neighboring sulfonic acid groups affect both theconformation and stability of the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 89 publications
1
37
0
Order By: Relevance
“…was then obtained from the various optimized conformance structure energy calculations. These calculations heavily influence subsequent results in this study [16].…”
Section: Energy Calculationmentioning
confidence: 80%
See 3 more Smart Citations
“…was then obtained from the various optimized conformance structure energy calculations. These calculations heavily influence subsequent results in this study [16].…”
Section: Energy Calculationmentioning
confidence: 80%
“…The average and maximum barrier energies of phosphorylated nata de coco dimers was found to be approximately 5.3 and 12.5 J, respectively, far below the observed barrier energy of PFSA fragments and sPSO2. This shows that the backbone of pyranose rings are more flexible (less stiff) compared to PTFE backbones and sPSO2 [16,[21][22]. A possible explanation is that the majority of the hydrogen bonds formed in phosphorylated nata de coco are unaffected by rotation along central C-O bonds.…”
Section: Backbone Conformationmentioning
confidence: 97%
See 2 more Smart Citations
“…23 Dissipative particle dynamics (DPD) simulations have shown that the sPSO 2 -220's polyelectrolyte backbone is significantly stiffer as for example the polyethylene backbones of PAMPS or PSS. 24,25 Furthermore, due to the electron withdrawing sulfonyl group (-SO 2 -) the sulfonate group is especially acidic for sPSO 2 -220, which leads to high dissociation degrees of 54-61%, 26,27 in comparison to a dissociation degree of 33-38% for PSS or PAMPS. 28,29 C 14 TAB was chosen as surfactant, as it is the shortest surfactant in the C n TAB series that forms stable films on its own.…”
Section: Introductionmentioning
confidence: 99%